1879 N.C. Sess. Laws 360 - (:unkn) unknown (My University, 1879)
Ch. 204, §§ 1-6: It shall be unlawful to take any fish of the kind known as perch or bream by shooting or netting in the day time or in any manner by fire light from any of said streams between the first day of May and the fifteenth day of August in each year.
Keywords: FISHING REGULATION